2020
DOI: 10.1039/d0cc00119h
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and orientation of organic semiconductor thin films by microcrystal electron diffraction and grazing-incidence wide-angle X-ray scattering

Abstract: The complementary methods of MicroED and GIWAXS provide insight into crystal structure arrangement in organic semiconductor thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…We demonstrated cryoFIB milled lamella give higher resolution data of better quality when compared to nanocrystals under the same imaging conditions. We showed that the low cost Ceta-D camera, generally accessible in a standard cryoEM setup, worked well for microED for well diffracting samples, as reported recently by others ( Hattne et al, 2019 ; Martynowycz et al, 2019 ; Wang et al, 2019 ; Levine et al, 2020 ). We show a better structure (2.0 Å) than that reported for lamella of proteinase K using Ceta-D detector (2.75 Å) ( Martynowycz et al, 2019 ).…”
Section: Resultssupporting
confidence: 83%
“…We demonstrated cryoFIB milled lamella give higher resolution data of better quality when compared to nanocrystals under the same imaging conditions. We showed that the low cost Ceta-D camera, generally accessible in a standard cryoEM setup, worked well for microED for well diffracting samples, as reported recently by others ( Hattne et al, 2019 ; Martynowycz et al, 2019 ; Wang et al, 2019 ; Levine et al, 2020 ). We show a better structure (2.0 Å) than that reported for lamella of proteinase K using Ceta-D detector (2.75 Å) ( Martynowycz et al, 2019 ).…”
Section: Resultssupporting
confidence: 83%
“…In order to further characterize the isolated compound, we used MicroED for high-resolution structure determination. There are several methods for preparing small molecule samples for the TEM, including applying powdered sample directly to the grid, applying a crystalline suspension to the grid followed by drying, and direct crystal growth on the grid by solvent evaporation (van Genderen et al, 2016;Gruene et al, 2018;Jones et al, 2018;Banihashemi et al, 2020;Levine et al, 2020). For this analysis, preparing the EM grids with the sample was performed by simply placing the grids in a small amount of material as described above, a process which took less than 1 min.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the recent development of techniques such as microcrystal electron diffraction (MicroED) have enabled the determination of the structures of both large biomolecules and small molecules in crystalline form (Gemmi et al, 2019;Nannenga and Gonen, 2019;Nannenga, 2020). Electron diffraction has been successfully applied to a wide variety of samples including proteins, peptides, small organic molecules, and inorganic materials (Mugnaioli et al, 2009(Mugnaioli et al, , 2012(Mugnaioli et al, , 2018Zhang et al, 2013Zhang et al, , 2018Nannenga et al, 2014a,b;Rodriguez et al, 2015;Simancas et al, 2016;van Genderen et al, 2016;Clabbers et al, 2017Clabbers et al, , 2020Krotee et al, 2017;Palatinus et al, 2017;Rozhdestvenskaya et al, 2017;Das et al, 2018;Gallagher-Jones et al, 2018;Gruene et al, 2018;Hughes et al, 2018;Jones et al, 2018;Liu and Gonen, 2018;Seidler et al, 2018;Brázda et al, 2019;Dick et al, 2019;Lanza et al, 2019;Warmack et al, 2019;Wennmacher et al, 2019;Xu et al, 2019;Zatsepin et al, 2019;Banihashemi et al, 2020;Levine et al, 2020;Zhu et al, 2020). A major benefit to this technique is that the micro and nanocrystals used for MicroED are several orders of magnitude smaller than those used in conventional X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9a] Microcrystal electron diffraction (MicroED) has recently emerged as aw ay to circumvent limitations related to crystal growth since it can allow highresolution structural data to be acquired on nanocrystalline samples. [10] In this contribution, we use ac ombination of divergent synthesis and MicroED to interrogate solid-state behavior in an ew family of expanded helicenes.T he quinone-and quinoxiline-containing helicenes 2-mon, 2-di, 3-mon,and 3-di (Scheme 1b)w ere targeted due to their electron deficiency, which tends to promote strong intermolecular interactions between p-systems. [8a,11] Then ew compounds were accessed via ah ighly selective oxidative dearomatization of electronrich 1a,w hich provided derivatives of the same or reduced symmetry.W hile uncontrollable crystallization kinetics consistently resulted in the formation of microcrystals that were unsuitable for single crystal X-ray diffraction, the application of MicroED enabled the rapid acquisition of high resolution data for all five helicenes.T his data revealed three different packing motifs,r epresenting four different space groups.…”
Section: Introductionmentioning
confidence: 99%